Time Synchronization for Digital Substation - Tripathi, Anju (My University, 2014)
In the present era of research and development, real time data synchronization is very important in digital substation. Time synchronization. In digital substation is required to ensure that devices have accurate time for system control and data acquisition. There are different types of time synchronization technologies like Global Positioning system (GPS), Inter range instrumentation- B Time code (IRIG-B), Simple Network Time Protocol (SNTP) and Precision Time Protocol (PTP) standardized by IEEE 1588. In the proposed thesis work all the above technologies has been studied and analyzed to get the best protocol on the basis of Time synchronization accuracy, High efficiency, adaptability and reliability for Digital substation. The second objective is to achieve redundancy in the best protocol. For this Network Redundancy protocol has been studied and implemented through two different protocols. Finally a case study has been done on SNTP protocol using SEL-2401 Satellite-synchronization clock.
ME, EIED
Keywords: IRIG-B; HSR PROTOCOL; IEEE1588